2012
DOI: 10.2164/jandrol.110.012583
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Plasma: An Essential Attribute to Spermatozoa

Abstract: The biochemical composition of seminal plasma (SP) is very complex and variable among species. Advances in reproductive technologies reveal SP as a nutritive-protective medium for sperm cells suspended in it, and some SP components are very important for sperm metabolism, as well as sperm function, survival, and transport in the female reproductive tract. Biochemistry of SP is a relatively modern but rapidly expanding field of research, particularly concerning the biological significance of the various biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
178
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(191 citation statements)
references
References 153 publications
(170 reference statements)
6
178
2
5
Order By: Relevance
“…The seminal plasma is composed of multiple ions, energy substrates, and organic compounds such as citric acid, lipids, amino acids, peptides, and low-and high-molecular weight proteins. These components support the survival of spermatozoa in the female reproductive tract and facilitate successful fertilization (Juyena & Stelletta 2012). We propose that seminal plasma contains kisspeptins, which are secreted by the epididymal epithelium (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…The seminal plasma is composed of multiple ions, energy substrates, and organic compounds such as citric acid, lipids, amino acids, peptides, and low-and high-molecular weight proteins. These components support the survival of spermatozoa in the female reproductive tract and facilitate successful fertilization (Juyena & Stelletta 2012). We propose that seminal plasma contains kisspeptins, which are secreted by the epididymal epithelium (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…The seminal plasma is a mixture of fluids secreted by the sexual glands (seminal vesicles, the prostate and the bulbourethral glands) and other male sexual organs (testis and epididymis) and provides a nutritive and protective medium for sperm after ejaculation (Juyena & Stelletta 2012). The presence of RNA molecules in human seminal plasma was first identified by Huang and coworkers (Huang et al 2009), and then confirmed by several studies (Huang et al 2009, Weber et al 2010, Wu et al 2012, Xiong 2014.…”
Section: Discussionmentioning
confidence: 96%
“…This could be mainly due to a membrane stabilizing property of nutrients made available by the EZ complex, causing lesser release of these enzymes in seminal plasma. The leakage of these enzymes proved to be an indicator of semen quality [63]. Testes and epididymides are considered to be the possible sources of these enzymes [64].…”
Section: Effect Of Anaerobic Probiotic On Rabbitmentioning
confidence: 99%